2014
DOI: 10.4067/s0718-95162014005000068
|View full text |Cite
|
Sign up to set email alerts
|

Pruning severity affects yield, fruit load and fruit and leaf traits of 'Brigitta' blueberry

Abstract: Pruning is crucial to balance productivity and fruit quality in blueberry orchards. Slight, conventional and severe pruning treatments were applied on 4-and 5-year old bluberry plants cultivar 'Brigitta' to evaluate their effect on yield, leaf area, gas exchange and fruit load as driver of fruit quality traits. Yield and berries per plant decreased with increasing pruning severity, whereas canopy leaf area increased. The resulting fruit load ranged from 0.2 to 1.4 fruit per cm 2 leaf area. Fruit weight, dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
(28 reference statements)
1
13
1
2
Order By: Relevance
“…The season average berry weight was also decreased by the heavy pruning treatment compared with other pruning intensities in 2013 and 2014, likely because much of the fruit ripened later in the season, when fruit size was smaller. In contrast to our results where heavy pruning decreased fruit size, Strik et al (2003) and Jorquera-Fontena et al (2014) found that heavy winter hand pruning increased berry weight compared with moderate hand pruning and no pruning in highbush blueberry. However, the removal of inflorescence buds during winter pruning would decrease inflorescence bud number and therefore berry number the following growing season, potentially increasing berry weight.…”
Section: Treatment Ycontrasting
confidence: 99%
“…The season average berry weight was also decreased by the heavy pruning treatment compared with other pruning intensities in 2013 and 2014, likely because much of the fruit ripened later in the season, when fruit size was smaller. In contrast to our results where heavy pruning decreased fruit size, Strik et al (2003) and Jorquera-Fontena et al (2014) found that heavy winter hand pruning increased berry weight compared with moderate hand pruning and no pruning in highbush blueberry. However, the removal of inflorescence buds during winter pruning would decrease inflorescence bud number and therefore berry number the following growing season, potentially increasing berry weight.…”
Section: Treatment Ycontrasting
confidence: 99%
“…Due to these changes, the skin of the 'Patriot' fruits was substantially thinner than in the 'Earliblue' cultivar. Many researchers report that V. corymbosum fruits are characterised by a double sigmoid growth pattern consisting of 3 stages differing in the length depending on the variety and environmental conditions (Godoy et al, 2008;Jorquera-Fontena et al, 2014). As pointed out by Brady (1987) and Giovannoni (2004), stage I is characterised by rapid cell division and dry weight gain and lasts from 25 to 35 days.…”
Section: Discussionmentioning
confidence: 98%
“…Jujube plants under C 1 pruning intensity had the highest yield, so pruning within a limited range of intensity had a positive effect. Jorquerafontena et al (2014) found that yield and berries per plant decreased with increasing pruning intensity.…”
Section: Discussionmentioning
confidence: 96%